Geomorphology of Desert Environments - Parsons, Anthony J.; Abrahams, A. D. (Springer Netherlands : Imprint: Springer, 2009)
About one-third of the Earth's land surface experiences a desert climate, and this area supports approximately 15% of the planet's population. This percentage continues to grow, and with this growth comes the need to acquire and apply an understanding of desert geomorphology. Such an understanding is vital in managing scarce and fragile resources and in mitigating natural hazards. This authoritative reference book is comprehensive in its coverage of the geomorphology of desert environments, and is arranged thematically. It begins with an overview of global deserts, proceeds through treatments of weathering, hillslopes, rivers, piedmonts, lake basins, and aeolian surfaces, and concludes with a discussion of the role of climatic change. Written by a team of international authors, all of whom are active in the field, the chapters cover the spectrum of desert geomorphology. Geomorphology of Desert Environments - Second Edition is thoroughly revised and extended with six new chapters, many new illustrations and expanded and updated references in each chapter. - The most comprehensive and up-to-date research-level treatment of desert geomorphology - Presented from a global perspective - Written by authoritative practitioners in the field From the reviews of the previous edition: "Geomorphology of Desert Environments is a worthy and desirable newcomer" Nature "... up-to-date expert reviews that together represent a comprehensive treatment of the state of knowledge in desert geomorphology." SciTech Book News.